Assessment of Alborz University of Medical Sciences Dental Students\' Knowledge of Medical Emergencies - Maryam Aghabarary; Mahsa Khedmatizare; Ali Esmaeili; Iman Shirinbak; Roohangiz Norouzinia (نشریه دانشگاه علوم پزشکی البرز)
Background and Aim: Lack of necessary awareness and misdiagnosis can have serious consequences in dental emergencies, potentially causing irreparable harm to the patient's health. This study aimed to assess dental students' knowledge at Alborz University of Medical Sciences regarding medical emergencies in 2019.